Enhancement of Oceanic Eddy Activity by Fine‐Scale Orographic Winds Drives High Productivity, Low Oxygen, and Low pH Conditions in the Santa Barbara Channel. Issue 12 (29th November 2022) - Kessouri, Fayçal; Renault, Lionel; McWilliams, James C.; Damien, Pierre; Bianchi, Daniele
Abstract: The Santa Barbara Channel is one of the most productive regions of the California Current System. Yet, the physical processes that sustain this high productivity remain unclear. We use a high‐resolution physical‐biogeochemical model to show that submesoscale eddies generated by islands are energized by orographic effects on the wind, with significant impacts on nutrient, carbon, and oxygen cycles. These eddies are modulated by two co‐occurring air‐sea‐land interactions: transfer of wind energy to ocean currents that intensifies ocean eddies, and a wind‐current feedback that tends to dampen them. Here we show that the dampening is overwhelmed by fine scale wind patterns induced by the presence of surrounding capes and islands. The fine‐scale winds cause an additional transfer of momentum from the atmosphere to the ocean that energizes submesoscale eddies. This drives upward doming of isopycnals in the center of the channel, allowing a more efficient injection of nutrients to the surface, and triggering intense phytoplankton blooms that nearly double productivity relative to the case without fine‐scale winds. The intensification of the doming effect by the wind‐curl and submesoscale eddies pumps deep low oxygen, acidic waters to the center of the cyclonic eddies. These eddies are then transported away from the Channel into the California Current, where they impact a wider area along the central coast, with potential ecological consequences. Our study highlights the important role of air‐sea‐land interactions in modulating coastal processes, and suggests that submesoscale resolving models are required to correctly represent coastal processes and their ecological impacts. Plain Language Summary: Surface waters in the Santa Barbara Channel of California are very rich in phytoplankton, the small algae responsible for photosynthesis in the ocean. This abundance is caused by winds, which pump deep water rich in nutrients to the surface each spring and summer, and by vortices of the size of few tens of km that form in the wake of the Channel Islands. In this study, we use very detailed simulations of the Santa Barbara Channel carried out on supercomputers to show that these vortices become much more intense when they interact with small‐scale patterns in the winds, such as strong jets that blow between capes and islands. We show that while the interactions between the surface currents and the atmosphere tend to slow down the vortices, the small‐scale winds actually accelerate them, making them stronger. These vortices in turn help pumping more waters rich in nutrients to the surface, fertilizing phytoplankton. This deep water is also poor in oxygen and acidic, and is often transported outside of the Santa Barbara Channel, where it could affect the behavior of marine animals that thrive in more oxygenated and less acidic waters. Key Points: Interaction of the low‐level wind with capes and islands enhances the transfer of energy from the atmosphere to the ocean The wind energizes submesoscale cyclonic eddies, enhancing productivity in the Santa Barbara Channel Submesoscale cyclonic eddies advect low oxygen, acidic waters beyond the Channel into the broader California Current